Sarcoidosis Associated with Oxaliplatin-Based Chemotherapy for Colorectal Cancer. (4th March 2014) - Choi, Ji Hoon; Shin, Jung A.; Park, Hye Kyeong; Kim, Su Young; Jung, Hoon; Lee, Sung-Soon; Lee, Hye Ran; Koo, Hyeon-Kyoung
Abstract : Acute lung injury occasionally occurs after chemotherapy, but pulmonary toxicities by oxaliplatin-based chemotherapy have rarely been identified. A 76-year-old female with rectosigmoid colon cancer presented with ongoing dyspnea after the eighth cycle of standard chemotherapy (5-fluorouracil, sodium folinic acid, and oxaliplatin: FOLFOX). Nodular consolidation progressed despite antibiotics and BAL fluid analysis was compatible with the diagnosis of sarcoidosis. Corticosteroid therapy rapidly improved the symptoms and radiographic findings. We report this first case of secondary sarcoidosis related to FOLFOX therapy with review of references.